Effect of chitosan on growth and productive parameters in broccoli plants (Brassica oleracea L. var. Calabrese) - Reyes-Perez, Juan; Murillo-Amador, Bernardo; Macias, Ramon; Menacé, Moisés; Aragón, Eréndira; Palacios-Espinosa, Alejandro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Biostimulants improve the absorption and assimilation of nutrients by plants, making them more tolerant to biotic or abiotic stress, improving their agronomic characteristics. Natural and biodegradable biostimulants such as chitosan have fungal and bactericidal activities and promote growth and crop yield, this is why, to evaluate the effect of chitosan application on growth and productive parameters of broccoli (Brassica oleracea L.), three concentrations of chitosan (T1 = 500 mg.L-1; T2 = 1000 mg.L-1; and T3 = 2000 mg.L-1) and a control treatment (T4 = distilled water), were applied by foliar spray when the true leaves unfolded, using a completely randomized design with 30 repetitions per treatment. The variables height of the plant, number of leaves per plant, diameter of the flowering stalk, diameter of the flowering head, length of the flowering stalk, total length of the flowering stalk, fresh biomass of the flowering head, of the root, and of the aerial part, total dry biomass and yield were measured. All the variables increased (P<0.05) as the chitosan dose increased, concluding that the application of chitosan to the broccoli crop is a viable alternative as a substitute for synthetic fertilizers.